ANALISIS DAYA SAING PARIWISATA UNTUK MENINGKATKAN EKONOMI DAERAH - Dewi Maharani; Harjoni Harjoni; Tri Widayati; Basnendar Herry Prilosadoso; Heppi Syofya (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze tourism competitiveness to improve the regional economy. To measure tourism competitiveness in this study using 8 indicators from the World Travel and Tourism Council (WTTC), including Human Tourism Indicator (HTI), Price Competitiveness Indicator (PCI), Infrastructure Development Indicator (IDI), Environment Indicator (EI), Technology Advancement Indicator (TAI), Human Resources Indicator (HRI), Openness Indicator (OI) and Social Development Indicator (SDI). The type of research used is quantitative descriptive. The data sources used in this study are secondary data. The analysis method used in this study is to calculate the tourism competitiveness index. The findings in this study are that all indicators used to measure the level of tourism competitiveness in tourist areas in Indonesia have increased in 2023 from the previous year 2022.